2002
DOI: 10.1016/s0027-5107(02)00189-6
|View full text |Cite
|
Sign up to set email alerts
|

An unusual mutation in RECQ4 gene leading to Rothmund–Thomson syndrome

Abstract: Rothmund-Thomson syndrome (OMIM #268400) is a severe autosomal recessive genodermatosis: characterised by growth retardation, hyperpigmentation and frequently accompanied by congenital bone defects, brittle hair and hypogonadism. Mutations in helicase RECQ4 gene are responsible for a subset of cases of RTS. Only six mutations have been reported, thus, far and each affecting the coding sequence or the splice junctions. We report the first homozygous mutation in RECQ4 helicase: 2746-2756-delTGGGCTGAGGC in IVS8 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 8 publications
(10 reference statements)
0
27
0
Order By: Relevance
“…The region is required for the initiation of DNA replication, in particular for chromatin binding of DNA polymerase ␣. In humans, mutations in RecQ4 are responsible for some cases of Rothmund-Thomson syndrome (2,16,20), suggesting that RecQ4 is important for preventing genome instability and that mutations in it might lead to cancer or premature aging (1,7,9). Here we report that vertebrate RecQ4 performs an essential role in the formation of replication machinery through interaction with Cut5.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The region is required for the initiation of DNA replication, in particular for chromatin binding of DNA polymerase ␣. In humans, mutations in RecQ4 are responsible for some cases of Rothmund-Thomson syndrome (2,16,20), suggesting that RecQ4 is important for preventing genome instability and that mutations in it might lead to cancer or premature aging (1,7,9). Here we report that vertebrate RecQ4 performs an essential role in the formation of replication machinery through interaction with Cut5.…”
mentioning
confidence: 73%
“…1A). A further database search with the full-length Xenopus sequence revealed that it shares the highest similarity with mammalian RecQ4, whose mutation has been implicated in the generation of some cases of Rothmund-Thomson syndrome in humans (2,16,20). Because the sequence shows greater similarity to that of metazoan RecQ4 than to that of yeast Sld2/Drc1, we hereafter call this gene product Xenopus RecQ4.…”
Section: Resultsmentioning
confidence: 99%
“…2,19 Molecular characterisation of transcripts has occasionally disclosed the effect of RECQL4 mutations overlooked by DNA analysis. 20 The current study shows that the functional effects of mutations identified by DNA analysis may be better interpreted by RNA analysis. Because of the above considerations, the clinical utility gene card for RTS 21 recommends that the characterisation of RECQL4 mutations should always include RNA analysis.…”
Section: Growth Parametersmentioning
confidence: 73%
“…Identification of two novel RECQL4 exonic SNPs and genomic characterization of the IVS12 minisatellite Received: October 24, 2002/ Accepted: November 21, 2002 MIM#268400; Kitao et al 1999b;Lindor et al 2000;Wang et al 2002;Balraj et al 2002), a rare autosomal recessive genodermatosis, which, in addition to the poikilodermatous rash, has a variable clinical presentation and is associated with genomic instability and predisposition to malignancy (Wang et al 2001).…”
mentioning
confidence: 99%
“…During RECQL4 gene mutation screenings of patients with a clinical diagnosis of RTS, we identified in the RECQL4 coding region two novel and one already described (Balraj et al 2002) single-nucleotide polymorphism (SNP) falling into predicted functional exonic splicing enhancers (ESEs). ESEs are cis-acting elements that function as binding sites for serine/arginine-rich (SR) proteins, a family of essential splicing factors that are also involved in alternative splicing regulation (Cartegni et al 2002).…”
mentioning
confidence: 99%